A new species of Creagrutus Günther (Characidae: Stevardiinae) from the Amazonian Piedmont of Colombia - Albornoz-Garzón, Juan G.; Acosta-Santos, Astrid; Bogotá-Gregory, Juan D.; Agudelo-Córdoba, Edwin (Zootaxa, 2020)
A new species of Creagrutus is described from the Amazonian Piedmont, Colombia. The new species can be distinguished from congeners by presenting the following unique combination of characters: a dark mid-lateral stripe starting at anteriormost scale of lateral line, a vertically elongated humeral blotch, absence of dark blotches on dorsal fin and at base of middle caudal-fin rays, a triangular dentigerous surface of the premaxilla, 5–6 dentary teeth, and 11–12 predorsal scales. Comparisons with congeners distributed in the piedmont region of Río Caquetá basin are presented and its relationships among species of Creagrutus is inferred from the available phylogenetic framework.